Level of Awareness among Parents at Taman Lembah Bujang towards Child Abuse / Siti Norsuliha Mohamad...[et al.] - Mohamad, Siti Norsuliha; Mustafa, Siti Fatihah; Mazlan, Nadya Mustika (2010)
The objectives of this research are to know the level of awareness among the parents at Taman Lembah Bujang towards the child abuse. It is also to determine the mechanism that the parents will know about the child abuse. A total respondent of 80 parents at Taman Lembah Bujang were selected to fill the sets of questionnaires that consist of 4 sections which are demographic factors (Section A), Level of Awareness (Section B), factor that lead to child abuse (Section C) and mechanism for know about the child abuse (Section D). The data was analyzed by Pearson Correlation and Stastical Package for Social Science (SPSS) version 16.0. The result indicates that there is relation between the dependent variable, which is the level of awareness and their independent variables which is the mechanism, type and factor that lead to child abuse.